Why Students with Severe Disabilities Are Not Being Placed in General Education Classrooms: Using the Frame of a Basic Change Model to Expand the Discussion. (March 2020) - Vandercook, Terri; Taub, Debbie; Loiselle, Tayler; Shopa, Amanda
This article addresses particular aspects of the Agran et al. identified determinants related to inclusive educational practices for students with severe disabilities. More specifically, this article focuses on perceptions of competency in students with severe disabilities and the resulting placement decisions, as well as facilitating systemic change to build inclusive systems. The discussion focuses on how the determinant related to perceptions of competency and the four elements of systems change identified by Agran et al. play a part in the ongoing lack of inclusion for these students. This response uses the frame of a basic change model to further the discussion on the important question of why students with severe disabilities are not being placed in general education classrooms.